The link between stress disorders and autonomic dysfunction in muscular dystrophy - Sabharwal, Rasna (Frontiers in Physiology, 2014)
Muscular dystrophy is a progressive disease of muscle weakness, muscle atrophy and cardiac dysfunction. Patients afflicted with muscular dystrophy exhibit autonomic dysfunction along with cognitive impairment, severe depression, sadness, and anxiety. Although the psychological aspects of cardiovascular disorders and stress disorders are well known, the physiological mechanism underlying this relationship is not well understood, particularly in muscular dystrophy. Therefore, the goal of this perspective is to highlight the importance of autonomic dysfunction and psychological stress disorders in the pathogenesis of muscular dystrophy. This article will for the first time - (i) outline autonomic mechanisms that are common to both psychological stress and cardiovascular disorders in muscular dystrophy; (ii) propose therapies that would improve behavioral and autonomic functions in muscular dystrophy.